INTESTINAL PARASITIC INFECTIONS IN A LOWINCOME URBAN COMMUNITY: PREVALENCE AND KNOWLEDGE, ATTITUDES AND PRACTICES OF INHABITANTS OF PARQUE OSWALDO CRUZ, RIO DE JANEIRO, BRAZIL - Ferraz Ignacio, Caroline; Martins de Oliveira Espíndola, Carina; de Fátima Leal Alencar, Maria; da Costa Lima, Mayra; Claudio Muniz, Luis; Carvalho de Vasconcellos, Maurício; Helena Féres Saad, Maria; Macedo de Lima Barata, Martha; Henrique Almeida de Moraes Neto, Antonio (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
Intestinal parasitic infections (IPIs) are present in Brazil from upper-to low-income communities, with varying infection estimates; however, they affect those living in urban and rural poverty more severely, without adequate access to consistently safe drinking water, sanitation, waste disposal, medical access and education. Estimates show the need for establishing infection prevalence and socioeconomic features, along with population knowledge, attitudes and practices (KAP) regarding IPIs. The purpose of this study is to assess the prevalence and KAP regarding IPIs of residents of an urban low-income community (Parque Oswaldo Cruz/Amorim) of the Complexo de Manguinhos, Rio de Janeiro, Brazil. The Lutz sedimentation technique was used for parasite detection (n=1,121) and, to obtain data on community KAP regarding IPIs, a KAP survey, adapted from Mello et al. was applied (n=505). An overall prevalence of 20.7% was detected with protozoa composing 92.9% (n=235) of the positive samples. Questionnaires revealed generally correct knowledge but with several inconsistencies, unawareness of the association between the etiological agent and the disease, and uncertainty regarding own knowledge of the subject. The population understood the importance of prevention and was willing to utilize prevention strategies despite being unsure of how to prevent infection. Further studies are required to investigate best practices for improving health equity, community health empowerment and IPIs prevention in Rio de Janeiro, Brazil.